Nature, Power, and Growth - Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2001)
This essay reviews the relationship between natural-resource abundance and economic growth around the world, and presents some new results. The principal reasons why resource-based production can inhibit economic growth over long periods are traced to the Dutch disease, neglect of education, rent seeking, and economic policy failures. Across a large number of countries in the period from 1965 to 1998, the share of the primary sector in the labour force is shown to be inversely related to exports, domestic and foreign investment, and education, and directly related to external debt, import protection, corruption, and income inequality. The cross-sectional data show, moreover, that the share of the primary sector in the labour force is inversely related to per capita growth across countries. None of this lies in the nature of things, however. What seems to matter for economic growth is not the abundance of natural resources per se, but rather the quality of their management, and of economic management and institutions in general.
Keywords: 330; Natural resources; rent seeking; economic growth